INVESTIGATION OF THE USABILITY OF CUBIC BORON NITRIDE CUTTING TOOLS AS AN ALTERNATIVE TO DIAMOND CUTTING TOOLS - Islak, S.; Kir, D.; Celik, H. (Polska Akad Nauk, Polish Acad Sciences, Inst Metall & Mater Sci Pas, 2013)
Diamond and cubic boron nitride (cBN) cutting segments were produced using hot pressing technique for this study to be used in cutting natural stone. cBN grains were added to bronze powder, the chosen matrix, at a rate of 0%, 20%, 40%, 60%, 80%, and 100% (according to percentage by weight). Segments were produced under a pressure of 35 MPa, at a sintering temperature of 600 degrees C, over a sintering time of 3 minutes. The cutting properties of the produced segments were determined by cutting Ankara andesite. A Scanning Electron Microscope (SEM) and an X-Ray Diffractometer (XRD) were used to analyse the microstructure, phase compound, and wear surfaces of each segment type.
Keywords: cBN cutting tools; hot-pressing technique; wear